Buah Pandan Laut (Pandanus tectorius) menjadi Hard Candy - Yuliza Maulidar; Lia Handayani (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
Pandanus Tectorius this type of mengrove plant that grows both wild and cultivated has several benefits ranging from leaves, stems, and fruit. According to Hani and Dendang (2008) the benefits of marine pandanus gardens from an ecological aspect include preventing coastal abrasion, reducing the impact of tides on terrestrial ecosystems. The process of making hard candy by heating sugar (48.78%) in water (24.4%) lime (2.43%) and oranges plus all treatments and the adding sea pandan fruit extract (24.39%) while continuously strirring until homo geneous, when it is cooked, let it sit for 10 minutes before first and then candy dough is in the mold and allowed to harden, then it is taken from the application to be packaged. The assessment of this preference test is based on the sensing process. The things that are assessed include: appearance, aroma, taste and texture. The test was carried out by 30 panelists with a hedonic scale of 1-5. In general, hard candy is only known as a food product as a sources of calories and doest not contain antioxidants. Antioxidants are inhibitor compounds that inhibit, slow down, or delay the reaction of oxides in foof or the human body by donating electrons or transferring hydrogen atoms to free radicals. Antioxidants can prevent other cells in the body’s organs from free radicals (Pardede, 2013).